'I'm sorry, I've no doubt I've offended someone here': interactional repair in a public mesage board discussion thread - Kleinke, Sonja (Saarland working papers in linguistics, 2008)
This study analyzes a complete discussion thread of a Public Internet Message Board with regards to the use of interactional repair strategies. It considers micro- as well as macro-level strategies and compares these to findings in natural interaction. This study shows that different micro and macro strategies are implemented in different stages of the discussion. Participants use the special framing conditions of public Internet Message Boards to carefully renegotiate their interpersonal relationships after conflictive passages on a one-to-one basis: this cannot be accomplished in the same way in natural poly- or multilogues.
Gesehen am 03.09.2019